Hybrid solutions for didactics in higher education: An interdisciplinary workshop of 'Visual Storytelling' to develop documentation competences - Marina De Rossi; Emilia Restiglian (Universidad de Deusto, 2019)
The article reports on the results of a Design-Based Research path realized through a workshop about the "Visual Storytelling" (VS). The workshop aimed to develop teacher's professional competences about digital narrative documentation to be certified through the Open Badge system. The interdisciplinary design was developed according to the ICT-TPACK framework between the two courses "Methodologies, Didactics and Technologies for Teaching" and "Educational Research" in the Master's degree in Primary Teaching. 32 students were involved to deal with the documentation of some real educational experiences observed at school. They were asked to fill a semi-structured questionnaire at the end of the workshop. Other data came from a rubric used to evaluate VS products from three different points of views (students' self-assessment; university teachers; school teachers). The workshop stimulated the students to use technologies creatively, critically and reflectively to develop an authentic task realizing a VS product. According to the students' opinion, the workshop also facilitated collaborative processes as well as skills of self-assessment and the personalization of learning. Received: 08 October 2018 Accepted: 20 March 2019 Published online: 29 May 2019